2017
DOI: 10.1007/s11432-016-9229-y
|View full text |Cite
|
Sign up to set email alerts
|

Encoding syntactic representations with a neural network for sentiment collocation extraction

Abstract: Sentiment collocation refers to the collocation of a target word and a polarity word. Sentiment collocation extraction aims to extract the targets and their modifying polarity words by analyzing the relationships between them. This can be regarded as a basic sentiment analysis task and is relevant in many practical applications. Previous studies relied mainly on the syntactic path, which is used to connect the target word and the polarity word. To deeply exploit the semantic information of the syntactic path, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Convolutional Netural Network (CNN, for short) and Recurrent Neural Network (RNN, for short) have been proved to be effective models for effective classification tasks in the nonlinear system. In terms of the emotional classification of the text, some models of cyclic neural network and convolutional neural network are used to classify the emotions of the short text, and excellent results were obtained [16][17][18][19][20]. However, due to the gradient explosion problem of RNN model, LSTM and GRU models based on the RNN model are more commonly used models [21][22][23][24][25].…”
Section: Research On Text Classification Model Based On Deepmentioning
confidence: 99%
“…Convolutional Netural Network (CNN, for short) and Recurrent Neural Network (RNN, for short) have been proved to be effective models for effective classification tasks in the nonlinear system. In terms of the emotional classification of the text, some models of cyclic neural network and convolutional neural network are used to classify the emotions of the short text, and excellent results were obtained [16][17][18][19][20]. However, due to the gradient explosion problem of RNN model, LSTM and GRU models based on the RNN model are more commonly used models [21][22][23][24][25].…”
Section: Research On Text Classification Model Based On Deepmentioning
confidence: 99%
“…In addition to the aforesaid tasks, Pozzi et al [1] consolidated other tasks including emotion detection suggested in 2005 [23], opinion spam detection instigated in 2008 [24], multi-lingual sentiment analysis initiated in 2009 [25], multi-modal sentiment analysis introduced in 2011 [26] and opinion summarization [20]. Furthermore, there are other tasks like sentiment dynamic tracking [27] popularized in 2012 and sentiment collocation [28] that involves the extraction of the targets and related opinion terms based on their correlation.…”
Section: Tasks Of Sentiment Analysismentioning
confidence: 99%
“…[20] et al designed Friend++, a hybrid multi-individual recommendation model that integrates a weighted average method into the random walk framework by seamlessly employing social ties, behavior context, and personal information. References [21], [22] construct neural network models to mine deep information between features respectively from emotional analysis and semantics of social relationships.…”
Section: Related Workmentioning
confidence: 99%